(untitled) - Levetin, Estelle (New York, 2006)
Plants and society is organized into 26 chapters that are grouped into seven units. The first nine chapters cover the basic botany found in an introductory course. However, even in these chapters we have included many applied topics; some in the boxed essays but others derectly in the chapters text,...
Keywords: Botany,Botany, economic,Plants; Social aspects